1997
DOI: 10.1063/1.364391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implant temperature on transient enhanced diffusion of boron in regrown silicon after amorphization by Si+ or Ge+ implantation

Abstract: Si wafers were preamorphized by either Si or Ge ions at temperatures between 5 and 40°C. The diffusion of low energy 4 keV B implants into the preamorphized Si was studied in order to monitor the flux of interstitials from the end of range EOR region toward the surface. Transient enhanced diffusion TED in the regrown silicon was observed for all implants. Increasing the implantation temperature of the Si implant by as little as 15°C can result in a marked decrease in the magnitude of the interstitial flux flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Furthermore, Jones et al 11 reported that low-temperature amorphizing implants led to dislocation loops which did not hamper the flow of interstitials across the amorphous/crystalline interface. As the Si ϩ implant in our work was performed using liquid-nitrogen cooling, this mechanism could also contribute to increased arsenic diffusion in the Si ϩ implanted layers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Jones et al 11 reported that low-temperature amorphizing implants led to dislocation loops which did not hamper the flow of interstitials across the amorphous/crystalline interface. As the Si ϩ implant in our work was performed using liquid-nitrogen cooling, this mechanism could also contribute to increased arsenic diffusion in the Si ϩ implanted layers.…”
Section: Discussionmentioning
confidence: 99%
“…They are elongated along <110> directions and lie in {311} planes and were therefore identified as {311} defects. These defects are known to be formed at the EOR after recrystallization of amorphous layer created by Si or Ge implantation [18,19]. In the case of Li implantation at liquid nitrogen temperature, they were not observed after annealing at 600 °C for 30 minutes [12].…”
Section: Buried Amorphous Layermentioning
confidence: 99%
“…Of the various choices for pre-amorphization species, Ge þ is the most promising amorphization agent (Jones et al, 1997) primarily because it is known to result in lower sheet resistance than either argon or fluorine (Colombeau et al, 2004). The advantage of Ge over Si is that the former is a heavier atom and therefore, a lower implantation dose is sufficient to create a uniform amorphous layer.…”
Section: Concentration Concentrationmentioning
confidence: 99%